2018
DOI: 10.1111/his.13740
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eight melanocytic and neural crest‐associated markers in a well‐characterised series of 124 malignant peripheral nerve sheath tumours (MPNST): useful to distinguish MPNST from melanoma?

Abstract: MPNST (in NF1 and a sporadic setting) can quite often be positive for Melan-A, tyrosinase and MITF. Pathologists should be cognisant of these exceptions to prevent confusion with melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Additionally, the present immunostaining results (positive for S100, SOX10, and CD56 and negative for SMA and PNL2) were able to differentiate the tumor from amelanotic melanoma. The histological and immunohistochemical characteristics of this tumor were consistent with those of PNST in humans, dogs, and rats [2,5,7,9,14,15,18]. In addition to these findings, the pronounced invasiveness in combination with the bone destruction enabled us to confirm that the present tumor was an MPNST.…”
supporting
confidence: 78%
“…Additionally, the present immunostaining results (positive for S100, SOX10, and CD56 and negative for SMA and PNL2) were able to differentiate the tumor from amelanotic melanoma. The histological and immunohistochemical characteristics of this tumor were consistent with those of PNST in humans, dogs, and rats [2,5,7,9,14,15,18]. In addition to these findings, the pronounced invasiveness in combination with the bone destruction enabled us to confirm that the present tumor was an MPNST.…”
supporting
confidence: 78%
“…The diagnosis of MPNST continues to be challenging and problematic despite improvement in immunohistochemical and molecular diagnostic tools for sarcomas. [3]. The pathology of this patient's tumor was described as an epithelioid neoplasm with surrounding fibrosis, with myxoid appearance and scattered mitotic figures (Figure 1), which is consistent with MPNST histology described in the literature.…”
Section: Discussionsupporting
confidence: 84%
“…In conclusion, this study found that 20 percent of MPNST, including more than 60 percent of NF1-associated cases, showed diffuse immunostaining with melan-A. This could lead to misdiagnosis and pathologists should be aware that this marker is not genetically specific for melanoma [3].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Diagnosis of MPNST is challenging due to the lack of pathognomonic histopathologic features, specific immunophenotype, or diagnostic molecular signatures 14 . In particular, differentiation between MPNST and spindle cell/sarcomatoid melanoma is notoriously difficult, as these tumours may share strikingly similar histomorphology and immunophenotype 16,17 . S100 and SOX10 are often the only melanocytic/schwannian markers expressed in these tumours, 17,18 and about half of MPNSTs even lack expression for at least one of these markers 17,19–21 .…”
Section: Introductionmentioning
confidence: 99%